Oxygen uptake, acid-base balance and anaerobic energy system contribution in maximal 300 - 400 m running in child, adolescent and adult athletes - Vilmi, N.; Äyrämö, S.; Nummela, A.; Pullinen, T.; Linnamo, V.; Häkkinen, K.; Mero, A. A. (Journal of Athletic Enhancement, 2016)
Objective: The purpose of this study was to investigate oxygen uptake, acid-base balance and energy system contributions during and after short maximal running in adult (n=8), adolescent (n=8) and child (n=8) male athletes. Methods: The tests included a maximal time trial of 400 m, 350 m and 300 m for different age groups respectively and a VO2max running test on a 200 m indoor track. Capillary blood samples to analyse pH and lactate were taken before and after the time trial. Energy system contributions were estimated using the accumulated oxygen deficit (AOD) method. Results: Peak oxygen uptake (VO2peak) during the time trial was the lowest in children (53.1 ± 4.6 ml/kg/min) compared to adolescents (59.9 ± 3.7 ml/kg/min, P<0.01) and to adults (60.7 ± 2.4 ml/kg/ min, P<0.01). After the time trial minimal blood pH was the lowest in adults (6.97 ± 0.06) compared to adolescents (7.14 ± 0.07, P<0.05) and children (7.18 ± 0.03, P<0.001) and maximal blood lactate was the greatest in adults (17.4 ± 1.8 mmol/l) compared to adolescents (13.3 ± 3.7 mmol/l, P<0.05) and children (10.2 ± 1.1 mmol/l, P<0.01). The estimated anaerobic energy percentage during the time trial was the greatest in adults (53 ± 5%) compared to adolescents (44 ± 7%, P<0.05) and children (45 ± 5%, P<0.05). Conclusion: The present data demonstrated that adult and adolescent male athletes achieved greater oxygen uptake than child athletes during maximal 52-54 s running and adult athletes used mainly anaerobic energy and achieved greater acidosis than adolescents and children, who used mainly aerobic energy.